2015
DOI: 10.1111/tri.12528
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 deficiency attenuates ischemia-reperfusion injury after liver transplantation in mice

Abstract: SummaryLiver ischemia-reperfusion injury (IRI) is a major cause of morbidity and mortality after resection surgery, liver transplantation, and hemorrhagic and septic shock. Mir-155 is upregulated by a broad range of inflammatory mediators, and it has been demonstrated to be involved in both innate and adaptive immune responses. However, the role of mir-155 in liver IRI has never been investigated. In this study, mir-155 deficiency protected mice from liver IRI, as shown by lower serum alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Significant changes have been found in the levels of miR-155 in the hippocampus and blood after cerebral ischemia injury [24]. In hepatic ischemia-reperfusion, the lack of miR-155 can upregulate SOCS-1 expression and reduce the hepatic damage [11]. Maf is a family described as transcriptional activators and MafB plays a crucial part in mediating the inflammatory reaction in immune cells [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant changes have been found in the levels of miR-155 in the hippocampus and blood after cerebral ischemia injury [24]. In hepatic ischemia-reperfusion, the lack of miR-155 can upregulate SOCS-1 expression and reduce the hepatic damage [11]. Maf is a family described as transcriptional activators and MafB plays a crucial part in mediating the inflammatory reaction in immune cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nazari-Jahantigh et al [32] have also confirmed that miR-155 can attenuate the signaling of proinflammatory factor NF-κB by directly inhibiting the expression of BCL-6. Tang et al [11] have identified that miR-155 deficient can upregulate the expression of IL-10 and downregulate the expression of TNFα, IL-6, and IL-12p40 by decreasing ALT levels, so as to regulate the inflammatory reaction and stimulate innate immune to ameliorate liver ischemia. Consistently, our study demonstrated that systematic subjection to miR-155 inhibitor noticeably reduced ischemia-triggered proinflammatory cytokines IL-1β, IL-6, and TNF-α levels and inflammatory enzymes iNOS and COX-2 levels in CIR injury models in vitro and in vivo, while MafB inhibition or miR-155 overexpression can obviously reverse the impact of anti-miR-155 on inhibiting inflammation and then further augment CIR injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, IL‐2 signal is enhanced by SOCS1 downregulation. miR‐155 deficiency also attenuates liver ischemia‐reperfusion injury through upregulation of SOCS1, which was associated with promotion of M2 macrophage polarization and suppression of Th17 differentiation …”
Section: Socs1 and T Cellsmentioning
confidence: 99%
“…miR-155 deficiency also attenuates liver ischemia-reperfusion injury through upregulation of SOCS1, which was associated with promotion of M2 macrophage polarization and suppression of Th17 differentiation. (41) SOCS1 and Anti-Tumor Immunity SOCS1 is now considered to be an immune checkpoint molecule for anti-tumor immunity, because SOCS1 negatively regulates signaling of IFN-c and IL-12, essential cytokines for anti-tumor immunity. Previously, we and others showed that SOCS1silenced DCs induce stronger anti-tumor immunity.…”
Section: Socs1 and T Cellsmentioning
confidence: 99%